2013
DOI: 10.1016/j.devcel.2013.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type-Specific Profiling of Gene Expression and Chromatin Binding without Cell Isolation: Assaying RNA Pol II Occupancy in Neural Stem Cells

Abstract: SummaryCell-type-specific transcriptional profiling often requires the isolation of specific cell types from complex tissues. We have developed “TaDa,” a technique that enables cell-specific profiling without cell isolation. TaDa permits genome-wide profiling of DNA- or chromatin-binding proteins without cell sorting, fixation, or affinity purification. The method is simple, sensitive, highly reproducible, and transferable to any model system. We show that TaDa can be used to identify transcribed genes in a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
408
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(422 citation statements)
references
References 79 publications
14
408
0
Order By: Relevance
“…S4), and all available information on ey function, including that from ey mutants (Callaerts et al, 2001), expression of dominant-negative ey forms (Morante et al, 2011) or RNAi-mediated ey and toy knockdowns (our unpublished data), is compatible with these genes not playing a direct role in lamina development, at least during larval stages. Also, neither tsh nor its paralog tio is expressed in the OPC NE (Southall et al, 2013; data not shown), although cells of the OPC NE are ready to respond to tsh expression by proliferating and blocking lamina differentiation (supplementary material Fig. S5).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…S4), and all available information on ey function, including that from ey mutants (Callaerts et al, 2001), expression of dominant-negative ey forms (Morante et al, 2011) or RNAi-mediated ey and toy knockdowns (our unpublished data), is compatible with these genes not playing a direct role in lamina development, at least during larval stages. Also, neither tsh nor its paralog tio is expressed in the OPC NE (Southall et al, 2013; data not shown), although cells of the OPC NE are ready to respond to tsh expression by proliferating and blocking lamina differentiation (supplementary material Fig. S5).…”
Section: Discussionmentioning
confidence: 96%
“…However, there are several profound differences. Neither ey nor toy, the two Pax6 genes positioned at the top of the genetic hierarchy of eye development, is expressed during lamina development (Callaerts et al, 2001;Morante et al, 2011;Southall et al, 2013) (supplementary material Fig. S4), and all available information on ey function, including that from ey mutants (Callaerts et al, 2001), expression of dominant-negative ey forms (Morante et al, 2011) or RNAi-mediated ey and toy knockdowns (our unpublished data), is compatible with these genes not playing a direct role in lamina development, at least during larval stages.…”
Section: Discussionmentioning
confidence: 99%
“…It is called TRIBE, T argets of R NA-binding proteins I dentified B y E diting, and is particularly well-suited to identify target RNAs within small numbers of cells. TRIBE is conceptually similar to the DNA-oriented ‘targeted DamID’ (van Steensel and Henikoff, 2000, Southall et al, 2013) and entails in vivo expression of a fusion protein between an RBP and the catalytic domain of the RNA-editing enzyme ADAR. The transcriptome is then sequenced to identify novel editing events introduced by the RPB-ADARcd.…”
Section: Introductionmentioning
confidence: 99%
“…The PCR products are hybridized to microarrays or used directly for deep sequencing. In summary, DamID requires relatively low input material and processing time, is cost-effective and accurately reflects ChIP results (Southall et al, 2013). …”
Section: Introductionmentioning
confidence: 99%